Teoretická a praktická náplň oboru klinická embryologie - Trávník, P; Hampl, A; Hűttelová, R; Malenovská, A; Priesnitz, J; Rejthar, D; Záková, J (Ceska gynekologie, 2013)
Clinical embryology is in whole Europe respected health care specialization. The specialists in this field are certified by the European Society of Human Reproduction and Embryology (ESHRE). In the Czech Republic the specialization has been formally established by the Government Order No 31/ 2010 after 30 years unformal existence. Concurrently with the wide development of new techniques in assisted reproduction, there is necessary to define the content of clinical embryology as a health care, scientific and educational discipline. The definition authorized by the Committee of Association of Reproductive Embryology (ARE) is given in this article..
Keywords: embryologie; Reproduction; klinické kompetence; Clinical Competence; lidé; rozmnožování; Embryology; Evropa; Humans; Europe